2010
DOI: 10.1159/000314915
|View full text |Cite
|
Sign up to set email alerts
|

Public Understanding of Risks from Gene-Environment Interaction in Common Diseases: Implications for Public Communications

Abstract: Background/Aims: Public understanding of the relationship between health behaviors and genes is likely to affect the motivational impact of learning information about one’s own genes. Extant research has featured difficulty measuring public understandings of this relationship. This essay explores public understanding of the relationship between genes and behavior, especially with regard to the mathematical relationships to risk concept. It contributes a psychometrically valid scale for measuring beliefs about … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 85 publications
2
36
0
Order By: Relevance
“…This was reinforced by the finding that most had never heard the term "epigenetics" and, when asked what topics of genetics they would be interested in learning about, many responded that they wanted to know "how environmental pollutants could affect their genes". Our findings echo a summary of a recent study by Condit et al (2011) that explored the public understanding of genes and the environment. Using surveys and mathematical relationships of risk, Condit concluded that the perception of how the environment affects genes and the nature of its additive process on health is not easily understood.…”
Section: Discussionsupporting
confidence: 87%
“…This was reinforced by the finding that most had never heard the term "epigenetics" and, when asked what topics of genetics they would be interested in learning about, many responded that they wanted to know "how environmental pollutants could affect their genes". Our findings echo a summary of a recent study by Condit et al (2011) that explored the public understanding of genes and the environment. Using surveys and mathematical relationships of risk, Condit concluded that the perception of how the environment affects genes and the nature of its additive process on health is not easily understood.…”
Section: Discussionsupporting
confidence: 87%
“…6 However, many posit that realization of these benefits will be challenged by lay audience's beliefs about the role of genetics and the difficulties of conveying information about complex gene-by-environment influences on disease. 7 Adapting this information for global contexts characterized by low literacy and diverse cultural norms will also increase the challenge.…”
Section: Introductionmentioning
confidence: 99%
“…Data from Condit (Condit, 2010;Condit & Shen, 2011) suggest that most individuals have separate mental tracks for considering how behavior affects health outcomes and for how genes affect health outcomes (such as cancer). Moreover, most are adept at switching from the genetic track to the behavior track.…”
Section: Om M U N Icatio N S a B O U T G E N E -E N V Iro N M E N Tmentioning
confidence: 99%